Two essays on poverty and economic development in brazilian municipalities - Scaraboto, Nícolas Volgarine (2021)
Although expermenting decline over the past decades, the number of people living below the poverty line is still alarming. According to IBGE, in 2015, the number of people below the poverty line was 13.5 million Brazilians, around 6.5% of the population. In addition to the material deprivations imposed on individuals, poverty can impair cognitive and socio- emotional development, especially of children, with reflections on human capital. Thus, understanding the dynamics of poverty is a necessity in order to find solutions to overcome it. This paper is composed of two essays. The first studies the effects of poverty on the quality of education as observed by the SAEB scores. For 5th grade students, the effect of a one percentage point change in the incidence of poverty reduces school performance by 1.2%. For 9th grade students, this effect reaches 1.1%. The second essay builds on the work of Ravallion (2012). It aims to assess why we do not see poverty convergence across brazilian municipalities. That is, why poorer municipalities are not experiencing a sharper reduction in poverty. The results suggest that the initial incidence distribution of poverty itself negatively affects both the growth of per capita income and the poverty reduction process.